Building professional knowledge of future technical translators (Pedagogy of Higher and Secondary Education, 2014)
Pyzina E. V. Building professional knowledge of future technical translators.The article discusses how its author built professional knowledge of future technical translators in the students of technical universities with the help of information technologies. The researcher both provides her readers with real examples of the learning forms, methods, and techniques used and describes the results she has obtained during the educational experiment.
Keywords: professional training; translator’s competencies; technical literature; technical university; professional knowledge; information technologies